Investment Risk Analysis Through Portfolio Diversification Using It Based Company’s Stocks and Cryptocurrency - Widodo, Iqbal; Mukti Soma, Abdul (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
Investment is an activity carried out for the purpose of gaining profit in the future by entrusting their assets to several assets such as stocks, securities such as deposits and bonds, property, precious metals, jewelry, foreign currencies, cryptocurrencies, commodities, startup companies, and so on. Stock investment is one of the investment options that is considered profitable because its value will go hand in hand with the company's performance from the stock, and also the value of regular dividends which are an added value to the profits obtained. Cryptocurrency is also now starting to become a new alternative in investment solutions because of its decentralization concept which makes cryptocurrency have very high volatility where it has a fairly high risk but also has a high return value. Due to the advantages and disadvantages of Stocks and cryptocurrencies, an idea emerged to be able to diversify between stocks and cryptocurrencies in order to find the best and most optimal investment results by creating a portfolio that is a combination of stocks and cryptocurrencies The results of this study are expected to be useful as a reference that can be used to set investment strategies for investors who are interested in investing in stocks and cryptocurrencies to get the most optimal results with the lowest risk.